Interleukin 1β and tumour necrosis factor α secreting cells are increased in the peripheral blood of patients with primary Sjögren's syndrome. Issue 4 (1st April 2003) - Willeke, P; Schotte, H; Schlüter, B; Erren, M; Becker, H; Dyong, A; Mickholz, E; Domschke, W; Gaubitz, M
Abstract : Objective: To study systemic alterations of cytokine secreting peripheral blood mononuclear cells (PBMC) in primary Sjögren's syndrome (pSS) and their relation to common clinical and immunological manifestations of this disease. Methods: PBMC spontaneously secreting tumour necrosis factor α (TNFα), interleukin 1β (IL1β), and interleukin 6 (IL6) were assessed by enzyme linked immunospot (ELISPOT) analysis in a cohort of 31 patients with pSS fulfilling the modified European classification criteria. Nineteen healthy volunteers served as controls. ELISPOT results were correlated with glandular and extraglandular manifestations and autoantibody titres—that is, rheumatoid factor (RF) isotypes, anti-Ro/SS-A, anti-La/SS-B as determined by an enzyme linked immunosorbent assay (ELISA) technique. Results: The number of TNFα and IL1β secreting cells was significantly higher in patients with pSS than in controls. No differences were detected in the number of IL6 secreting PBMC. Patients with recurrent parotid swelling (RPS) had a significantly increased number of IL1β secreting PBMC. Moreover, the number of IL1β secreting PBMC correlated with the disease duration ( r s =0.479; p<0.01) and with the concentration of IgM RF ( r s =0.63; p<0.01) and IgG RF ( r s =0.42; p<0.05). Other autoantibodies did not correlate with cytokine secreting PBMC. Conclusion: The increased systemic secretion of IL1β and TNFα in patients with pSS points to a pathogenic impact of these cytokines in this autoimmune disease. In particular the correlation of IL1β secreting PBMC with RPS and RF production indicates that IL1β is a crucial regulator in the development of local and systemic disease manifestations.